Association between genetic variants in DNA and histone methylation and telomere length. - Sangmi Kim; Christine G Parks; Zongli Xu; Gleta Carswell; Lisa A DeRoo; Dale P Sandler; Jack A Taylor (PLoS ONE)
Telomere length, a biomarker of aging and age-related diseases, exhibits wide variation between individuals. Common genetic variation may explain some of the individual differences in telomere length. To date, however, only a few genetic variants have been identified in the previous genome-wide association studies. As emerging data suggest epigenetic regulation of telomere length, we investigated 72 single nucleotide polymorphisms (SNPs) in 46 genes that involve DNA and histone methylation as well as telomerase and telomere-binding proteins and DNA damage response. Genotyping and quantification of telomere length were performed in blood samples from 989 non-Hispanic white participants of the Sister Study, a prospective cohort of women aged 35-74 years. The association of each SNP with logarithmically-transformed relative telomere length was estimated using multivariate linear regression. Six SNPs were associated with relative telomere length in blood cells with p-values<0.05 (uncorrected for multiple comparisons). The minor alleles of BHMT rs3733890 G>A (p = 0.041), MTRR rs2966952 C>T (p = 0.002) and EHMT2 rs558702 G>A (p = 0.008) were associated with shorter telomeres, while minor alleles of ATM rs1801516 G>A (p = 0.031), MTR rs1805087 A>G (p = 0.038) and PRMT8 rs12299470 G>A (p = 0.019) were associated with longer telomeres. Five of these SNPs are located in genes coding for proteins involved in DNA and histone methylation. Our results are consistent with recent findings that chromatin structure is epigenetically regulated and may influence the genomic integrity of telomeric region and telomere length maintenance. Larger studies with greater coverage of the genes implicated in DNA methylation and histone modifications are warranted to replicate these findings.